Accuracy of self-reported cancer treatment data in young breast cancer survivors - Kelly C. Gast; Elizabeth J. Cathcart-Rake; Aaron Norman; Leah Eshraghi; Nwamaka Obidegwu; Fergus Couch; Celine Vachon; Kathryn J. Ruddy (SpringerOpen, 2019)
Abstract Background Patient-reports of cancer treatments are sometimes used in oncology research and clinically when medical records are unavailable. We aimed to evaluate the accuracy of patient recall in this setting. Materials and methods Participants were recruited through an email request from the Dr. Susan Love Research Foundation Army of Women seeking women diagnosed with breast cancer under age 50 and within the past ten years, self-reporting to have been treated with chemotherapy. After informed consent, participants received a web-based survey that inquired about use of and type of chemotherapy and endocrine therapy received. Medical records were reviewed, and discrepancies were defined as patient-report of a different class of drug than documented in the medical record, failing to report a documented class of drug, or responding "don't know." Results Of 171 eligible participants, completed questionnaires and medical records were available for 102 (60%). Median age at diagnosis was 41 years (range 25-49), and median time from diagnosis was 65.5 months (range 7-131). Ninety-two percent had completed college. Receipt of chemotherapy was documented in the medical records of 100% of these women who self-reported a personal history of chemotherapy, and there was also 98% concordance regarding receipt of endocrine therapy (yes vs. no). However, discrepancies were identified in 29% of patients regarding chemotherapy types. Time since diagnosis did not increase the likelihood of discrepancies. Conclusion Highly educated young women diagnosed with breast cancer more than five years prior accurately report whether or not they received broad systemic treatment categories. However, self-reports regarding specific drugs should be confirmed by medical record review.